2018
DOI: 10.1037/pst0000175
|View full text |Cite
|
Sign up to set email alerts
|

Therapist empathy and client outcome: An updated meta-analysis.

Abstract: Put simply, empathy refers to understanding what another person is experiencing or trying to express. Therapist empathy has a long history as a hypothesized key change process in psychotherapy. We begin by discussing definitional issues and presenting an integrative definition. We then review measures of therapist empathy, including the conceptual problem of separating empathy from other relationship variables. We follow this with clinical examples illustrating different forms of therapist empathy and empathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
197
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(237 citation statements)
references
References 115 publications
(76 reference statements)
3
197
2
3
Order By: Relevance
“…The participants felt the counsellors had knowledge and deep understanding of their experience which contributed to the empathy they displayed. A meta-analysis of studies exploring the effect of psychotherapy therapist empathy on client outcomes, reported that the level of empathy displayed by a therapist is a moderately strong predictor of therapy outcome [28], and future studies could explore in more depth the importance of empathy and embodiment in participant/counsellor relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The participants felt the counsellors had knowledge and deep understanding of their experience which contributed to the empathy they displayed. A meta-analysis of studies exploring the effect of psychotherapy therapist empathy on client outcomes, reported that the level of empathy displayed by a therapist is a moderately strong predictor of therapy outcome [28], and future studies could explore in more depth the importance of empathy and embodiment in participant/counsellor relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses and reviews have stressed the importance of empathy (Elliott et al, 2018) and related qualities, including positive regard (Farber et al, 2018), interpersonal skills (Wampold, 2017), genuineness (Kolden et al, 2018), and feedback (Norcross, 2002;Lambert et al, 2018). The meta-analyses (Elliott et al, 2018;Kolden et al, 2018;Farber et al, 2018;Tryon et al, 2018) discussed below consist mainly of cross-sectional studies. This is an important shortcoming, since psychotherapy is an ongoing process that requires repeated measures.…”
Section: Therapist Qualities Associated With Treatment Outcomementioning
confidence: 99%
“…Recent meta-analyses have related empathy (Elliott et al, 2018), congruence/genuineness (Kolden et al, 2018), positive regard (Farber et al, 2018), and goal consensus and collaboration (Tryon et al, 2018) to treatment outcome. Other therapist characteristics that may influence treatment outcomes were self-disclosure and immediacy (Hill et al, 2018), countertransference management (Hayes et al, 2018), and therapist and client emotional expression (Peluso & Freund, 2018).…”
Section: Therapist Qualities Associated With Treatment Outcomementioning
confidence: 99%
“…Having established that psychotherapy works well for most common mental health problems (Norcross & Lambert, 2018), and better than many other evidence-based medical practices (Wampold & Imel, 2015), we are also getting closer to understanding why psychotherapy works across different approaches. Some of the (pan-theoretical) process factors with the most promising evidence thus far are; a sound alliance between therapist and client (Flückiger et al, 2018); collecting and giving feedback on client progress using routine outcome monitoring (Lambert et al, 2018); therapist empathy (Elliott et al, 2018), facilitative interpersonal skills (Anderson et al, 2009) and cultivating client positive expectations (Constantino et al, 2018).…”
mentioning
confidence: 99%